Systematic review and meta-analyses of vitamin E alpha-tocopherol supplementation and blood lipid parameters in patients with diabetes mellitus - Mohammad, Abolfathi; Falahi, Ebrahim; Mohd Yusof, Barakatun Nisak; Nor Hanipah, Zubaidah; S., Mohd Redzwan; Mohamad Yusof, Loqman; Gheitasvand, Mohsen; Rezaie, Farahnaz (Elsevier, 2021)
Background and aims: The studies have shown that α-tocopherol supplementation could improve lipid profile in diabetes mellitus (DM) patients. Nonetheless, the result remains inconsistent. Therefore, this meta-analysis was performed to evaluate the efficacy of α-tocopherol supplement on lipid parameters in DM patients. Methods: We conducted an extensive search via Cochrane Library, PubMed, Scopus, and Web of Science databases to acquire the reported RCTs up to October 2020. Results: The results showed no effects of α-tocopherol supplementation on lipid profile in DM patients except when used ≥12 weeks. Conclusions: α-tocopherol supplementation in DM patients had no significant effect on lipid profiles.